Diversity and Aboveground Carbon Sequestration Potential of On-Farm Agroforestry Trees/shrubs Species in Rajaf County-South Sudan - Mayele, Joseph M.; Okullo, John B. L.; Tumwebaze, Susan B.; Bongo, Augustine L. (International Journal of Innovative Science and Research Technology, 2020)
Agroforestry (AF) trees have the potentials to sequester carbon in most farming systems especially in the face of the current climate change. The objective of this study was to estimate the diversity, abundance, and aboveground carbon sequestration potential of on-farm tree species in four different sites, Tokiman, Gumbo, Kolye West, and Kolye East with various agroforestry practices in Rajaf County, South Sudan. Three hundred and fifty-five AF trees were inventoried by non-destructive methods for diameter at breast height (DBH), height (H) and Crown width (CR) variables. Aboveground biomass analyzed using allometric models was converted to carbon stocks. The Shannon-Weiner indices for the AF sites indicated that C. limon, M. indica and P. guajava were more diverse in Tokiman and Gumbo sites. T. grandis was more diverse in Kolye East and Kolye West, with S. siamea only diverse in Kolye West. The diversity analyses also showed low values of (H’) for Gumbo and Tokiman as compared to those calculated for Kolye West and Kolye East. In addition, high levels of aboveground carbon sequestration were observed in Gumbo and Kolye East sites where tree species were relatively abundant. Kolye West, on the other hand, had very few but highly dominant AF tree species while Tokiman Islands with the most planted tree species had a rare agro-ecology that contributed less or nearly zero to aboveground carbon sequestration.
Keywords: Diversity index; carbon sequestration; agroforestry; above-ground biomass